Analisis Penggunaan E-Commerce Bagi UMKM Di Era Digital - Dicha Putri Rezkia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development of digital technology, especially e-commerce, has brought significant impacts to Micro, Small and Medium Enterprises (MSMEs). This research aims to identify the benefits and challenges of using e-commerce for MSMEs, as well as strategies that can be implemented to optimize the use of this platform. The research method used is a literature study to analyze information related to the benefits, challenges, and e-commerce promotion-strategies for MSMEs. The research findings show that e-commerce provides significant benefits, such as sales and market growth, and operational efficiency. However, MSMEs are also faced with challenges, such as the cost of technology adoption, low levels of digital literacy, and data security issues. To overcome these challenges, effective e-commerce promotion-strategies, such as building strong digital infrastructure, improving digital skills, and facilitating the use of e-commerce platforms, can be applied. The implication of this study is the importance of support and guidance for MSMEs in adopting e-commerce to remain competitive in the digital era.